Strength limits in mesoscaled 3Y-TZP ceramics for micro-surgical instruments. (March 2019) - Antolino, N.; Muhlstein, C.; Hayes, G.; Adair, J.; Bermejo, R.
Abstract: Micro-surgical instruments are a new application for mesoscale ceramics formed using the lost mold-rapid infiltration forming (LM-RIF) process. Instrument strength and reliability are the foremost concerns for this sensitive application. It is hypothesized that increasing grain size can improve the damage tolerance of the parts associated with the transformation toughening in the 3Y-TZP material, while retaining high strength. In this work, mesoscale bend bars (314 × 22 × 18 µm) of 3Y-TZP fabricated using the LM-RIF process were heat treated at 1400 °C for 1 h, 8 h, or 16 h, respectively, to obtain samples with different grain sizes. Strength tests were performed under three-point bending and results were evaluated using Weibull statistics. Fractographic and confocal Raman spectroscopic analyses were carried out to interpret the data. Experimental findings showed that the characteristic strength decreased with increasing grain size contrary to the damage tolerance hypothesis. An Orowan-Petch model was recalled to correlate the strength with the flaw size to grain size ratio. At fine grain sizes the strength was controlled by the flaws introduced by the LM-RIF process, whereas at large grain sizes the strength become more grain size controlled. Although larger-grained samples did have a higher propensity to transform, and thus increase toughening, exaggerated grain growth in some of the specimens tested caused an additional flaw population which led to an overall lower strength. Finally, based on the experimental observations and fracture mechanics considerations, we believe that an upper bound of ∼2.5 GPa exists for the strength of mesoscale as-fabricated 3Y-TZP ceramic parts. Graphical abstract: fx1